A study to Assess the Various Risk Factors Associated with Breast Cancer Among Patients Attending KIMS and Cancer Hospital in Hubli (Indian Journal of Public Health Research & Development, 2020)
Background: Breast cancer is the most common cancer in females worldwide, and the second leading causeof cancer deaths in women. The incidence is on the rise in India, and is the second most common malignancyamong the Indian women.Objective : To assess the risk factors of breast cancer among the patients attending cancer OPD in KIMSand cancer Hospital, Navanagar in Hubli.Materials and Methods: A cross sectional study was conducted to assess the various risk factors associatedwith breast cancer among patients attending KIMS and Cancer hospital in Navanagar, Hubli from May toJune of 2014. A pre-designed, pre-tested and semi structure questionnaire was used to collect the data.Results: Breast cancer was common in the age group of 50-70yrs, 36% of patients attained menarche 12 months, 98% of patients were unaware of breast self examination.Conclusions: Awareness about symptoms of breast cancer and self examination of the breast were lackingin the study population. Health care personnel should be trained to spread the awareness of breast cancerin the community and to identify the vulnerable groups at the primary care settings itself. As majority ofthe risk factors for breast cancer are modifiable, prevention and early detection of these risk factors alongwith increase awareness amongs the population will have significant impact on the occurrence of the breastcancer.
Keywords: Breast cancer, risk factor, breast self examination.